Military cartography of Serbian lands during the last Austro-Turkish war (1788–1791) - Horb, Yevhen (Balcanica Posnaniensia. Acta et studia, 2023)
The Austro-Turkish War of 1788–1791 has not yet been properly reflected in scientific literature despite the fact that in a certain way this last conflict between the Ottomans and the Holy Roman Empire „awakened the Balkans” and became a catalyst for the national liberation movement of the Serbs, which gained strength at the beginning of the 19th century. The territory of modern Serbia became a central theater of military actions in this difficult positional war, and those were the Serbs who ensured the success of many military operations of the Austrian troops. The war of 1788–1791 belonged to those conflicts, the history of which was written, so to speak, „in real time”, and this in many ways created certain stereotypes in the reproduction of the pattern of military actions. The one-sidedness and stereotyped nature of the narrative sources can be compensated by using large cartographic material – both published and stored in the archives of Austria, Hungary, Turkey, Ukraine, Russia, etc. Serbia as a theater of military actions is depicted on most of these maps and military topographical plans developed in the last quarter of the 18th century, but, with the exception of the Josephinian Land Survey, none of them have become the object of even cataloging and classification, not to mention its careful studying. Therefore, the00 proposed article is the first comprehensive attempt to summarize the information about cartographic sources regarding Serbian lands during the Austro-Turkish War of 1788–1791. As additional sources, to verify historical and geographical information, military topographical descriptions of Serbian lands compiled by the Austrian administration and periodicals of the war period were used.